The Effect of Arch Height and Material Hardness of Personalized Insole on Correction and Tissues of Flatfoot - Su, Shonglun (J Healthc Eng, 2017)
Flat foot is one of the common deformities in the youth population, seriously affecting the weight supporting and daily exercising. However, there is lacking of quantitative data relative to material selection and shape design of the personalized orthopedic insole. This study was to evaluate the biomechanical effects of material hardness and support height of personalized orthopedic insole on foot tissues, by in vivo experiment and finite element modeling. The correction of arch height increased with material hardness and support height. The peak plantar pressure increased with the material hardness, and these values by wearing insoles of 40° were apparently higher than the bare feet condition. Harder insole material results in higher stress in the joint and ligament stress than softer material. In the calcaneocuboid joint, the stress increased with the arch height of insoles. The material hardness did not apparently affect the stress in the ankle joints, but the support heights of insole did. In general, insole material and support design are positively affecting the correction of orthopedic insole, but negatively resulting in unreasonable stress on the stress in the joint and ligaments. There should be an integration of improving correction and reducing stress in foot tissues.